A reluctance to assimilate - Oded Stark; C. Simon Fan (University of Warsaw, Centre of Migration Research (CMR), 2006)
Quite often, migrants appear to exert little effort to absorb the mainstream culture and to learn the language of their host society, even though the economic returns (increased productivity and enhanced earnings) to assimilation are high. We show that when interpersonal comparisons affect individuals' wellbeing and when a more intensive assimilation results in migrants' comparing themselves more with the richer natives and less with fellow migrants, then the effort extended to assimilate will be muted.
Keywords: F22; J15; J24; J61; O15; Z10; 330; Migrants' behavior; The effort to assimilate; Income gains; Social proximity; Interpersonal comparisons; Deprivation losses; Migranten; Einwanderung; Soziale Integration; Theorie